An intelligent under frequency load shedding scheme for islanded distribution network - Laghari, J.A.; Mokhlis, Hazlie; Halim Abu Bakar, A.B.; Karimi, M.; Shahriari, A. (2012)
In islanding mode, system frequency is severely disturbed due to imbalance between generation and load demand resulting in overloading or loss of generation cases. In order to cope with these events, under-frequency load shedding scheme (UFLS) is applied to stabilize the frequency. This paper presents an intelligent under frequency load shedding scheme implemented on mini-hydro operating in islanded mode. The proposed UFLS scheme consists of a fuzzy logic load shedding controller (FLLSC) with load shedding controller module (LSCM). The FLLSC by measuring frequency and rate of change of frequency estimates the amount of load to be shed. The LSCM sheds the load estimated by FLLSC. This scheme is tested for event based and response based cases. The results have shown that proposed load shedding scheme successfully estimates the amount of load to be shed and stabilizes the frequency for these cases.